Exploring the Implementation of Merdeka Curriculum In Rural Madrasah - Hasanah, Uswatun; Arrasyid, Agung (Tarbawy : Jurnal Pendidikan Islam, 2025)
Although the Independent Curriculum has been introduced as a new policy to encourage flexibility, independent learning, and character building, its implementation in various educational units, particularly rural madrasas, still faces many obstacles. Most previous research has focused on urban schools, while studies examining the implementation of the Independent Curriculum in the context of rural madrasas, particularly in the subject of the Qur'an and Hadith, are still limited. This study aims to explore the implementation of the Independent Curriculum in Al-Qur'an and Hadith learning at Madrasah Aliyah Hidayatul Mubtadiin, South Lampung. The research approach used was descriptive qualitative, with data collection techniques through interviews, observation, and documentation involving the madrasah principal and two Al-Qur'an and Hadith teachers. The results showed that the implementation of the Independent Curriculum is still partial. Teachers do not fully understand the learning outcomes, still apply traditional lecture methods, and use conventional assessments that focus on written tests. Furthermore, limited infrastructure and digital access also hamper learning innovation. In the context of the Quran and Hadith subject, this curriculum actually opens up significant opportunities to integrate cognitive aspects (tahfidz) with moral reflection (tadabbur) and character-based learning. Therefore, ongoing teacher training, the development of contextual teaching modules based on Islamic values, and policy support that supports equitable distribution of madrasah education in rural areas are necessary.